2012
DOI: 10.1186/2046-2395-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a metabolic memory to early-life dietary restriction in male C57BL/6 mice

Abstract: Background: Dietary restriction (DR) extends lifespan and induces beneficial metabolic effects in many animals. What is far less clear is whether animals retain a metabolic memory to previous DR exposure, that is, can early-life DR preserve beneficial metabolic effects later in life even after the resumption of ad libitum (AL) feeding. We examined a range of metabolic parameters (body mass, body composition (lean and fat mass), glucose tolerance, fed blood glucose, fasting plasma insulin and insulin-like growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…This switch allowed thorough examination of persistence of the CR-induced effects upon challenging conditions. Previous studies showed that favourable metabolic effects of CR, such as an improved glucose tolerance, are persistent after discontinuation of prolonged CR [26,27]. In our study, we have seen that most gene expression profiles, relative abundance of microbial genera and levels of metabolites adapted to patterns of the MF mice after the diet switch.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This switch allowed thorough examination of persistence of the CR-induced effects upon challenging conditions. Previous studies showed that favourable metabolic effects of CR, such as an improved glucose tolerance, are persistent after discontinuation of prolonged CR [26,27]. In our study, we have seen that most gene expression profiles, relative abundance of microbial genera and levels of metabolites adapted to patterns of the MF mice after the diet switch.…”
Section: Discussionsupporting
confidence: 61%
“…However, detailed insight into persistence of CR-induced effects upon challenging conditions is scarce [25]. It has been demonstrated that favourable metabolic effects are persistent after discontinuation of prolonged CR [26,27]. To what extent this 'metabolic memory' also applies to the colon, and whether CR-induced effects on markers of colonic health are persistent, is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The lifelong CR‐exposed mice in our aging cohort demonstrated their anticipation to receiving their daily food allotment by a burst in their activity level just prior to the regularly scheduled feeding (Van Norren et al., ). The hyperphagic response is an indicator that hunger persists even after a long‐term CR (Hambly, Mercer, & Speakman, ) and is maintained until body weight reaches the level of the ad libitum ‐fed animals (Selman & Hempenstall, ). It is followed by a dramatic weight gain, adipose tissue expansion, and hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that some physiological effects of dietary restriction, the most well-studied method to extend lifespan, are retained after this treatment is ended. For example, dietary restricted mice that are subsequently switched to an ad libitum diet retain significantly improved markers of glucose metabolism for months after this dietary modulation [40, 41]. In contrast though, the switch from dietary restricted to ad libitum feeding has also been shown to rapidly increase oxidative damage and alter the transcriptome to that of mice fed ad libitum their entire life [42, 43].…”
Section: Discussionmentioning
confidence: 99%